(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Public procurement constitutes a cornerstone of governance and economic development in India, with the L1 (Lowest Bidder) tendering system serving as the dominant mechanism for awarding public contracts. While L1 tendering is intended to promote transparency, competition, and fiscal prudence, its excessive reliance on the lowest financial bid has increasingly raised concerns regarding service quality, accountability, and institutional reliability. This paper critically examines the structural limitations of L1 tendering through a case study of the Staff Selection Commission’s (SSC) examination contract awarded to Eduquity Career Technologies. Using a qualitative case study methodology, the paper analyses the tender evaluation process and the subsequent conduct of SSC computer-based examinations conducted between July and August 2025. Despite scoring lower on technical parameters than established service providers such as Tata Consultancy Services (TCS), Eduquity secured the contract due to its significantly lower bid under the prescribed 70:30 technical–commercial weighting framework. The examinations were marked by widespread administrative and technical failures, including system crashes, biometric verification errors, and exam cancellations, leading to nationwide protests by candidates and public acknowledgment of mismanagement by the SSC Chairman. The study argues that rigid adherence to L1 tendering in high-stakes public services prioritizes short-term cost savings over long-term public value. It concludes by advocating procurement reforms that incorporate historical performance, institutional credibility, and stronger accountability mechanisms to ensure reliable and equitable service delivery.